FEASIBILITY OF TECHNICAL AND MANAGEMENT ASSISTANCE (ATEG) IN THE SOCIO-PRODUCTIVE DYNAMICS OF FAMILY FARMERS IN THE AMAZONIAN AGROECOSYSTEMS OF BORBA/AM (REMUNOM, 2026)
This study presents a qualitative search of the socio-environmental development of family farming influenced by the educational process of the Technical and Management Assistance Program (ATeG) of the Brazilian Confederation of Agriculture and Livestock (CNA) through the National Rural Learning Service (Senar) in agroecosystems. Based on field research, we analyzed the functioning of Amazonian agroecosystems in two rural settlements of agrarian reform in the municipality of Borba, state of Amazonas, Brazil, the PA Piaba and the PA Puxurizal. The analysis of the socio-productive dynamics allowed us to understand the theoretical and empirical composition of the process of maintaining agroecosystems, highlighting the complexity of the social actors, who jointly shape the environment under the influence of a Social Nucleus of Agroecosystem Management (NSGA). The results describe the distinctions and comparisons that represent the social category in the rural environment. In this sense, family farming systematizes a complex symbiosis, which maintains the joint relationship of sustainable ways and means of life, the territory and its territorialities, access to public policy, production, diversity, insertion in markets, etc., in an Amazonian typology recognized in the socio-environmental characteristics of the agroecosystems worked as an alternative way of life.